Performance gaps and improvement plans from a 5-hospital simulation programme for anaesthesiology providers: a retrospective study. (9th February 2017) - DeMaria, Samuel; Levine, Adam; Petrou, Philip; Feldman, David; Kischak, Patricia; Burden, Amanda; Goldberg, Andrew
Abstract : Background: Simulation is increasingly employed in healthcare provider education, but usage as a means of identifying system-wide practitioner gaps has been limited. We sought to determine whether practice gaps could be identified, and if meaningful improvement plans could result from a simulation course for anaesthesiology providers. Methods: Over a 2-year cycle, 288 anaesthesiologists and 67 certified registered nurse anaesthetists (CRNAs) participated in a 3.5 hour, malpractice insurer-mandated simulation course, encountering 4 scenarios. 5 anaesthesiology departments within 3 urban academic healthcare systems were represented. A real-time rater scored each individual on 12 critical performance items (CPIs) representing learning objectives for a given scenario. Participants completed a course satisfaction survey, a 1-month postcourse practice improvement plan (PIP) and a 6-month follow-up survey. Results: All recorded course data were retrospectively reviewed. Course satisfaction was generally positive (88–97% positive rating by item). 4231 individual CPIs were recorded (of a possible 4260 rateable), with a majority of participants demonstrating remediable gaps in medical/technical and non-technical skills (97% of groups had at least one instance of a remediable gap in communication/non-technical skills during at least one of the scenarios). 6 months following the course, 91% of respondents reported successfully implementing 1 or more of their PIPs. Improvements in equipment/environmental resources or personal knowledge domains were most often successful, and several individual reports demonstrated a positive impact on actual practice. Conclusions: This professional liability insurer-initiated simulation course for 5 anaesthesiology departments was feasible to deliver and well received. Practice gaps were identified during the course and remediation of gaps, and/or application of new knowledge, skills and resources was reported by participants.